2020
DOI: 10.1021/acs.jpcc.0c06032
|View full text |Cite
|
Sign up to set email alerts
|

Improved High Rate Performance and Cycle Performance of Al-Doped O3-Type NaNi0.5Mn0.5O2 Cathode Materials for Sodium-Ion Batteries

Abstract: O3-type layered transition metal oxides have shown great promise as high-capacity cathode materials for sodium-ion batteries in large-scale energy storage, due to their low cost and the abundance of sodium resources. However, the limited interlayer spacing and the unstable structure of the O3 phase result in inferior cycling stability and poor rate capability, which could even hinder their practical application process. Hereby, we present that doping with nonelectrochemically active Al in NaAl x (Ni 0.5 Mn 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 41 publications
(55 reference statements)
0
23
0
3
Order By: Relevance
“…After linear fitting between Z ′ (real part of impedance, Ω) and ω –1/2 (frequency, Hz), σ (Warburg factor, Ω s –1/2 ) is obtained as the value of the slope, as shown in Figure b. The Na + diffusion coefficients ( D ) of the three samples are calculated based on EIS spectra and eq S1 in the Supporting Information. The D Na + value of the Bir-TMA electrode is calculated as 4.79 × 10 –12 cm 2 s –1 , which is much higher than those of Bir-Na (3.8 × 10 –13 cm 2 s –1 ) and Bir-H (2.15 × 10 –13 cm 2 s –1 ) (Table S1). We found that D Na + of Bir-H is slightly less than that of Bir-Na.…”
Section: Results and Discussionmentioning
confidence: 99%
“…After linear fitting between Z ′ (real part of impedance, Ω) and ω –1/2 (frequency, Hz), σ (Warburg factor, Ω s –1/2 ) is obtained as the value of the slope, as shown in Figure b. The Na + diffusion coefficients ( D ) of the three samples are calculated based on EIS spectra and eq S1 in the Supporting Information. The D Na + value of the Bir-TMA electrode is calculated as 4.79 × 10 –12 cm 2 s –1 , which is much higher than those of Bir-Na (3.8 × 10 –13 cm 2 s –1 ) and Bir-H (2.15 × 10 –13 cm 2 s –1 ) (Table S1). We found that D Na + of Bir-H is slightly less than that of Bir-Na.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The 3D NG-loaded vertical nanosheet structure of the CoMnO/NC electrode provides a shorter pathway for both charge transfer and ion diffusion, along with larger active surface areas. In view of high specific capacity and superior rate capacity of the NG/CoMnO/NC composite electrode, it is essential to investigate the capacitive effect, which is quite relative and sensitive to surface regions . The CV measurement is further performed at various sweep rates from 0.1 to 1 mV s –1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In view of high specific capacity and superior rate capacity of the NG/CoMnO/NC composite electrode, it is essential to investigate the capacitive effect, which is quite relative and sensitive to surface regions. 45 The CV measurement is further performed at various sweep rates from 0.1 to 1 mV s −1 . Two pairs of redox peaks involving active metallic oxides are observed in the CV curves shown in Figure 7c.…”
Section: Electrochemical Characterization and Analysismentioning
confidence: 99%
“…[79] Al 3+ doped in the TM layer could induce a decrease in the thickness of the TMO 6 octahedron and increase the d-spacing of the Na diffusion layer due to the higher bond energy of Al−O (501.9 ± 10.6 kJ mol −1 ) and reduced Al−O bond length. [86,88] Furthermore, the lower electronegativity of Al also increases the ionic bonding strength during cycling. [87] Additionally, Al 3+ (radius: 0.535 Å) can also be introduced into the TM layer to decrease the number of Mn 3+ (radius: 0.645 Å), thereby mitigating undesired J-T distortion, resulting in much more moderate structural transition.…”
Section: Metallic Elemental Doping/ Substitutionmentioning
confidence: 99%